Hubungan Dinamis Antara Volume Perdagangan Saham, Nilai Tukar, Jakarta Islamic Indeks dengan Indeks LQ45 Menggunakan Vector Autoregressive (VAR) Di Bursa Efek Indonesia Periode 2017-2020 - Yenni Arfah; Andri Soemitra (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine the short-term effect of the relationship between Stock Trading Volume, Exchange Rate, Jakarta Islamic Index, and LQ45 Index on the Indonesia Stock Exchange for the 2017-2020 period. The population in this study is 208 time series data by including the entire population into the sample, which is 208 time series data. VECM is one of the econometric models used in analyzing the data in this study. Based on the research the hypothesis is accepted because the variables of Jakarta Islamic Index and LQ45 stock trading volume have an effect, while other variables do not, so the hypothesis is rejected.Keywords : Stock Trading Volume, Exchange Rate, Jakarta Islamic Index, LQ45 Index, VECM